DESAIN DAN UJI COBA LEMBAR KERJA PESERTA DIDIK BERBASIS LEARNING CYCLE 5E PADA MATERI LARUTAN PENYANGGA - Utami, Reka Pramanda (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research was instigated by the lack of availability teaching materials that could help students in the learning process, and the unavailability of using student workbook Learning Cycle 5E based. This research aimed at knowing the validity and practicality level ofstudent workbook Learning Cycle 5E based on Buffer Solution lesson. It was R&D (Research and Development) with 4-D (Define, Design, Develop, Disseminate) model. It was administered at State Senior High School 10 Pekanbaru. The subjects of this research were student workbook media design experts, learning material experts, chemistry subject teachers, and students. The object was student workbook Learning Cycle 5E based on Buffer Solution lesson. The data were obtained directly from questionnaire. The instruments of collecting the data were validity and practicality test questionnaires. The data then were analyzed by using Descriptive qualitative and quantitative analysis techniques. The produced workbook was tested, and it was valid with 90.9% percentage (very valid), and practical with 90.66% percentage (very practical). Based on these results, it could be concluded thatstudent workbook Learning Cycle 5E basedwas valid and practical on Buffer Solution lesson, so it was appropriate to be an additional teaching material for teachers at school.